2009
DOI: 10.1108/00070700910992925
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the differences in environmental impacts between organic and conventional farming

Abstract: Purpose -This paper aims to perform a meta-analysis of the literature comparing the environmental impacts of organic and conventional farming and linking these to differences in management practises. The studied environmental impacts are related to land use efficiency, organic matter content in the soil, nitrate and phosphate leaching to the water system, greenhouse gas emissions and biodiversity. Design/methodology/approach -The theoretic framework uses the driver-state-response framework and literature data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
184
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(228 citation statements)
references
References 83 publications
8
184
1
6
Order By: Relevance
“…Although there is some evidence that soil carbon concentrations are higher in soils managed organically than in those from integrated or conventional (nonorganic) farming (6,(8)(9)(10), other studies have not found such differences (11,12). Because of these inconsistent findings, advantages and disadvantages of the organic farming system vs. integrated or conventional production are hotly debated (11,13).…”
mentioning
confidence: 93%
“…Although there is some evidence that soil carbon concentrations are higher in soils managed organically than in those from integrated or conventional (nonorganic) farming (6,(8)(9)(10), other studies have not found such differences (11,12). Because of these inconsistent findings, advantages and disadvantages of the organic farming system vs. integrated or conventional production are hotly debated (11,13).…”
mentioning
confidence: 93%
“…As documented by Mondelaers et al (2009), nitrate leaching levels on organic and conventional farms varied between 0 and 152 mg N/l, the latter being an outlier. The EU directive 1991 prescribes a maximum nitrate leaching level of 50 mg N/l.…”
Section: Minmentioning
confidence: 99%
“…For each of the two quality traits (health or environment), two attributes were included in the choice experiment, of which one triggers desirable (positive) expectations and the other undesirable (negative). The choice of the attributes (and their levels) was the result of careful deliberation between the choice experiment preconditions and objective scientific boundaries, the latter based upon an extensive literature review (Hoefkens et al, 2009 andMondelaers et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…If the meaning was clearer, labels could add complementary, focused information to brand information. One perspective is suggested by Mondelaers et al (2009b) highlighting the contribution to the natural biodiversity as an advantage of organic products.…”
mentioning
confidence: 99%
“…For example, policy makers could explore how to transform greater agro-biodiversity and natural biodiversity (Mondelaers et al 2009b) into consumer benefits.…”
mentioning
confidence: 99%